Corticosteroid and platelet-rich plasma injection therapy in tennis elbow (lateral epicondylalgia): a survey of current UK specialist practice and a call for clinical guidelines. Issue 21 (6th November 2013) - Titchener, Andrew G; Booker, Simon J; Bhamber, Nivraj S; Tambe, Amol A; Clark, David I
Abstract : Background: Tennis elbow is a common condition with a variety of treatment options, but little is known about which of these options specialists choose most commonly. Corticosteroid injections in tennis elbow may reduce pain in the short-term but delay long-term recovery. We have undertaken a UK-wide survey of upper limb specialists to assess current practice. Methods: Cross-sectional electronic survey of current members of the British Elbow and Shoulder Society (BESS) and the British Society for Surgery of the Hand (BSSH). Results: 271 of 1047 eligible members responded (25.9%); consultant surgeons constituted the largest group (232/271, 85%). 131 respondents (48%) use corticosteroid injections as their first-line treatment for tennis elbow. 206 respondents (77%) believed that corticosteroid injections are not potentially harmful in the treatment of tennis elbow, while 31 (11%) did not use them in their current practice. In light of recent evidence of the potential harmful effects of corticosteroid therapy, 136 (50%) had not changed their practice while 108 (40.1%) had reduced or discontinued their use. 43 respondents (16%) reported having used platelet-rich plasma injections. Conclusions: Recent high-quality evidence that corticosteroids may delay recovery in tennis elbow appears to have had a limited effect on current practice. Treatment is not uniform among specialists and a proportion of them use platelet-rich plasma injections.